2010
DOI: 10.1007/s10803-010-1155-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Pervasive Developmental Disorder Not Otherwise Specified Less Stable Than Autistic Disorder? A Meta-Analysis

Abstract: We reviewed the stability of the diagnosis of pervasive developmental disorder not otherwise specified (PDD-NOS). A Medline search found eight studies reiterating a diagnostic assessment for PDD-NOS. The pooled group included 322 autistic disorder (AD) and 122 PDD-NOS cases. We used percentage of individuals with same diagnose at Times 1 and 2 as response criterion. The pooled Relative Risk was 1.95 (p < 0.001) showing that AD diagnostic stability was higher than PDD-NOS. When diagnosed before 36 months PDD-NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
4
33
1
2
Order By: Relevance
“…Consistent with the previous literature on the reliability of the PDD-NOS diagnosis in young children, our metaanalysis did not support the discriminant and predictive validity of this category. Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the previous literature on the reliability of the PDD-NOS diagnosis in young children, our metaanalysis did not support the discriminant and predictive validity of this category. Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups.…”
Section: Discussionsupporting
confidence: 88%
“…Based on these two studies, there does not appear to be evidence for qualitatively discrete groups (i.e., autism versus PDD-NOS), but differences appear to be quantitative Turner, et al, 2006). A recent meta-analysis (Rondeau et al, 2010) conducted on the eight longitudinal studies on PDD-NOS that have been published from 1996 to 2009 showed that PDD-NOS diagnosis was less stable than autistic disorder diagnosis. When established before 36 months, the overall stability rate was 35% at 3-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…There has been some concern that diagnosing a child with ASD may result in some false positives, particularly in the more mild cases or very young children (Rondeau et al, 2011). However, given the potential effects of ASD on the individual, the family, and the larger community, and the success of early intervention, it seems unwise and potentially detrimental to delay intervention or adopt the " wait and see if ASD develops " approach.…”
Section: Treat Behavioural Functioningmentioning
confidence: 99%
“…The consequences of these changes are not yet known and there has been great concern regarding whether the new criteria threaten service delivery and eligibility. For example, despite that children with less severe symptoms of ASD are often amenable to intervention and greatly benefi t from increased support, many of these individuals may no longer qualify for ASD services (Rondeau, Klein, Masse, Bodeau, Cohen, & Guil é , 2011). Current research suggests that some individuals with a DSM-IV diagnosis of autism may no longer meet criteria for ASD in the DSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that, while a diagnosis of autistic disorder is relatively stable, there is poor diagnostic stability for children who are high functioning and/or who present with fewer ASD traits such as in Pervasive Developmental Disorder-Not Otherwise Specifi ed (PDD-NOS) or Asperger ' s Syndrome (AS) as classifi ed in DSM IV (Rondeau, Klein, Masse, Bodeau, Cohen, & Guil é , 2011;Woolfenden, Sarkozy, Ridley, & Williams, 2012). Successful intervention could be hypothesized to produce this diagnostic instability.…”
Section: Developmental Trajectory (Natural History or Prognosis)mentioning
confidence: 99%